Hernia repair prevalence by age and gender among the Australian adult population from 2017 to 2021 - Thi Nga Le; Mohammad Afshar Ali; Svetla Gadzhanova; Renly Lim; Indu Bala; Kumsa Netsanet Bogale; Marianne Gillam (Critical Public Health)
Despite of high annual rate of surgery worldwide, few national-level studies have explored the epidemiological aspects of various types of hernia repairs. Our study aims to examine the 5-year prevalence of hernia repairs in Australian adults. The number of hernia repair surgeries for femoral, inguinal, incisional, other abdominal, and epigastric hernias were extracted from the Australian Institute of Health and Welfare (AIHW) database from financial year (FY) FY2017 to FY2021. We calculated age-specific prevalence and prevalence ratio (PR) with a 95% confidence interval (CI) to compare the prevalence of hernia repairs by age group and sex. The highest prevalence per 100,000 population of hernia repairs was found in inguinal (223), followed by epigastric (111), other abdominal (59), incisional (52), and femoral hernia (10). People over 65 years old had highest PR of hernias. There was a gender-wise variation across types of hernia procedures. Around 89.6% of patients with inguinal hernia repairs were males, while only 10.4% were females. The PR was lower in males for femoral and incisional hernia when compared two genders with corresponding age groups. Women in the pregnancy group (20–39 years) had a high risk of ventral hernia repair when compared to males. Groups of patients who have higher risks of hernia repair should be prioritized for healthcare service delivery, but more research is needed in hernia epidemiology, in Australia and internationally. Also, our study could serve as a national and international reference for other hernia repair studies where healthcare system is comparable.